Experimental Warming Hastens Physical Dormancy Break and Germination in Tropical Fabaceae - Jaganathan, Ganesh K.; Biddick, Matthew (Frontiers in Plant Science, 2021)
Climate warming may threaten the germination strategies of many plants that are uniquely adapted to today’s climate. For instance, species that employ physical dormancy – the production of seeds that are impermeable to water until high temperatures break them, consequently synchronizing germination with favorable growing conditions – may find that their seeds germinate during unfavorable or potentially fatal periods if threshold temperatures are reached earlier in the year. To explore this, we subjected the seeds of five species with physical dormancy (from the genera Abrus, Bauhinia, Cassia, Albizia and Acacia) to ‘mild’ (+2°C) and ‘extreme’ (+4°C) future warming scenarios and documented their germination over 2 years relative to a control treatment. Under current climatic conditions, a proportion of seeds from all five species remained dormant in the soil for 2 years. A mild warming of 2°C had little to no effect on the germination of 4 of the 5 study species. Contrastingly, an extreme warming of 4°C dramatically increased germination in all five species within the first year, indicating a reduction in their ability to persist in the soil long-term. Cassia fistula was particularly susceptible to warming, exhibiting a similar increase in germination under both mild and extreme warming relative to control. Our findings suggest that climate warming in the tropics may cause the seeds of species that rely on physical dormancy to stagger the risk of unsuccessful germination across years to leave soil seed banks prematurely – the long-term implications of which remain unknown.